2001
DOI: 10.1002/nau.1007
|View full text |Cite
|
Sign up to set email alerts
|

NK2 tachykinin receptors mediate contraction of the pig intravesical ureter: Tachykinin‐induced enhancement of non‐adrenergic non‐cholinergic excitatory neurotransmission

Abstract: The current study was designed to characterize the functionally active tachykinin receptors involved in tachykinin-elicited contractions in the pig intravesical ureter, and to investigate the possible modulation exerted by the natural tachykinins substance P (SP) and neurokinin A (NKA) on the non-adrenergic non-cholinergic (NANC) excitatory ureteral neurotransmission. In pig intravesical ureteral strips pretreated with phosphoramidon (10(-5) mol/L) to block the endopeptidase activities, isometric force recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Different peptides released from CSPA are involved in the nonadrenergic noncholinergic (NANC) neurotransmission of the urinary tract. Thus, in the pig intravesical ureter, neurokinin A (NKA) is involved in the NANC excitatory transmission (Bustamante et al, 2000), producing a smooth muscle contraction via activation of NK 2 receptors (Bustamante et al, 2001). VIP and PACAP produce relaxation in the urinary tract either by a direct action on the smooth muscle cells or by indirect effects mediated through NO release from autonomic intramural neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Different peptides released from CSPA are involved in the nonadrenergic noncholinergic (NANC) neurotransmission of the urinary tract. Thus, in the pig intravesical ureter, neurokinin A (NKA) is involved in the NANC excitatory transmission (Bustamante et al, 2000), producing a smooth muscle contraction via activation of NK 2 receptors (Bustamante et al, 2001). VIP and PACAP produce relaxation in the urinary tract either by a direct action on the smooth muscle cells or by indirect effects mediated through NO release from autonomic intramural neurons.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that tachykinins cause a direct contraction of the pig intravesical ureter via NK-2 receptors. SP and NKA were shown to enhance the NANC excitatory neurotransmission of the pig intravesical ureter [78] . Peptide-containing nerves VIP, NPY, CGRP and SP were all demonstrated particularly in the lower human ureter [11] .…”
Section: Neuropeptidesmentioning
confidence: 99%
“…Nitric oxide (NO) and unknown nature mediator/s are involved in the non‐adrenergic non‐cholinergic (NANC) inhibitory neurotransmission of the pig intravesical ureter . Peptides as substance P or neurokinin A evoke a direct contraction through smooth muscle NK 2 receptors, whereas vasoactive intestinal peptide (VIP) or pituitary adenylate cyclase‐activating polypeptide 38 (PACAP 38) relax the intravesical ureter through smooth muscle VIP/PACAP receptors …”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) and unknown nature mediator/s are involved in the non-adrenergic non-cholinergic (NANC) inhibitory neurotransmission of the pig intravesical ureter. 18 Peptides as substance P or neurokinin A evoke a direct contraction through smooth muscle NK 2 receptors, 20 whereas vasoactive intestinal peptide (VIP) or pituitary adenylate cyclase-activating polypeptide 38 (PACAP 38) relax the intravesical ureter through smooth muscle VIP/PACAP receptors. 21 In the current study, BK evoked a potent contraction on ureteral strip basal tension, which was not changed as a consequence of urothelium mechanical removal, thus suggesting the involvement of smooth muscle receptors in such a response.…”
Section: Discussionmentioning
confidence: 99%